Graphdiyne supported Ag–Cu tandem catalytic scheme for electrocatalytic reduction of CO2 to C2+ products. Issue 5 (17th January 2023) - Zhu, Qiuying; Hu, Yuying; Chen, Hongyu; Meng, Chen; Shang, Yizhu; Hao, Chengcheng; Wei, Shuxian; Wang, Zhaojie; Lu, Xiaoqing; Liu, Siyuan
Abstract : A highly dispersed Ag–Cu tandem catalyst relying on graphdiyne is committed to efficient conversion in the CO2 RR to C2+ products. Abstract : The electrochemical CO2 reduction reaction (CO2 RR) to added-value C2+ products is a worthy way to effectively reduce CO2 levels in the atmosphere. Cu nanomaterials have been proposed as efficient CO2 RR catalysts for producing C2+ products; however, the difficulties in controlling their efficiency and selectivity hinder their applications. Herein, we propose a simple routine to construct a graphdiyne (GDY) supported Ag–Cu nanocluster as a C2+ product-selective electrocatalyst and optimize the composition by electrochemical performance screening. The synthesized Ag–Cu nanoclusters are uniformly distributed on the surface of GDY with particle sizes constricted to 3.7 nm due to the strong diyne–Cu interaction. Compared to Cu/GDY, Ag–Cu/GDY tandem schemes exhibited superior CO2 RR to C2+ performance with a Faraday efficiency (FE) of up to 55.1% and a current density of 48.6 mA cm −2 which remain stable for more than 33 hours. Theoretical calculations show that the adsorption energy of CO is much higher on Cu (−1.066 eV) than on Ag (−0.615 eV), thus promoting the drift of *CO from Ag to Cu. Moreover, the calculations indicate that the key C–C coupling reaction of *CO with *COH is more favored on Ag–Cu/GDY than on the original Cu/GDY which contributes to the formation of C2+ products. Our findings shed light on a new strategy of combining a GDY support with a tandem catalytic scheme for developing new CO2 RR catalysts with superior selectivity and activity for C2+ products.